2021
DOI: 10.1016/j.jpain.2021.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Gender Biases in Estimation of Others’ Pain

Abstract: Caregiving and other interpersonal interactions often require accurate perception of others' pain from nonverbal cues, but perceivers may be subject to systematic biases based on gender, race, and other contextual factors. Such biases could contribute to systematic under-recognition and undertreatment of pain. In 2 experiments, we studied the impact of perceived patient sex on lay perceivers' pain estimates and treatment recommendations. In Experiment 1 (N = 50), perceivers viewed facial video clips of female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
81
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(90 citation statements)
references
References 69 publications
5
81
1
3
Order By: Relevance
“…If we analyze the daily dose according to sex in both treatments, men took more doses than women. Although these differences were significant only in the case of oxycodone/naloxone, this is consistent with published data suggesting that elderly patients and females may suffer from bias in pain assessments or dosing 23 this could be, as it was commented before because women had less intensity of pain than men. [23][24][25] Results of a genome wide association study suggested that differences experienced by men and women in chronic pain are likely to have a genetic basis.…”
Section: Treatment Durationsupporting
confidence: 91%
See 2 more Smart Citations
“…If we analyze the daily dose according to sex in both treatments, men took more doses than women. Although these differences were significant only in the case of oxycodone/naloxone, this is consistent with published data suggesting that elderly patients and females may suffer from bias in pain assessments or dosing 23 this could be, as it was commented before because women had less intensity of pain than men. [23][24][25] Results of a genome wide association study suggested that differences experienced by men and women in chronic pain are likely to have a genetic basis.…”
Section: Treatment Durationsupporting
confidence: 91%
“…Although these differences were significant only in the case of oxycodone/naloxone, this is consistent with published data suggesting that elderly patients and females may suffer from bias in pain assessments or dosing 23 this could be, as it was commented before because women had less intensity of pain than men. [23][24][25] Results of a genome wide association study suggested that differences experienced by men and women in chronic pain are likely to have a genetic basis. 29 By studying the daily dose depending on the duration of treatment, in both cases an increasing length of treatment increased the daily dose used, being significant, both positive correlations.…”
Section: Treatment Durationsupporting
confidence: 91%
See 1 more Smart Citation
“…We want to highlight that other threat recovery processes, in particular renewal (recovery threat responses within novel or dangerous context), might have contributed to the enhancement of threat responses by observation of others' US reactions. While our study was not designed to detect potential differences between male and female participants (when observing a US that is administered to a male demonstrator), we want to emphasize that differences in perceiving responses of males and females in pain (36) and identification with the demonstrator model (37) might influence observational reinstatement.…”
Section: Discussionmentioning
confidence: 99%
“…suggesting that men diagnosed with HS are more likely to undergo surgery than women. This is possibly due to men generally experiencing more severe disease [28,29], underestimation and dismissal of pain in female patients [30], or a lack of surgical expertise for female care due to common lesion localization to the inguinofemoral area [28], as well as low numbers of gynecologists providing HS surgery. This emphasizes the need for improved access to care for female patients through improved surgical expertise and increased awareness surrounding perception of pain in women.…”
Section: Principal Findingsmentioning
confidence: 99%